2012
DOI: 10.1111/j.1556-4029.2011.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Separation and Characterization of Cocaine and Cocaine Cutting Agents by Differential Mobility Spectrometry–Mass Spectrometry

Abstract: Forensic drug laboratories are inundated with cases requiring time-consuming GC- or LC-based chromatographic separations of submitted samples. High-throughput analytical methods would be of great practical utility within forensic drug analysis. Recently developed ion-mobility-based separation methods combined with mass spectrometry can often be used without chromatography, suppress chemical interferents of similar mass, and operate in seconds. We have evaluated differential mobility spectrometry-mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…1,33,34 However, other adulterants-especially other illicit substances or over-the-counter products-may be toxic and contribute to adverse effects. [29][30][31][32] Third, the route of cocaine administration can produce different types and levels of adverse effects. 1,25 Prior research suggests that intranasal use of powder cocaine may significantly increase the risk of an adverse reaction and snorting cocaine usually has a longer-lasting effect than does smoking it.…”
Section: Discussionmentioning
confidence: 99%
“…1,33,34 However, other adulterants-especially other illicit substances or over-the-counter products-may be toxic and contribute to adverse effects. [29][30][31][32] Third, the route of cocaine administration can produce different types and levels of adverse effects. 1,25 Prior research suggests that intranasal use of powder cocaine may significantly increase the risk of an adverse reaction and snorting cocaine usually has a longer-lasting effect than does smoking it.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to increase throughput for forensic purposes, Hall et al developed a novel method for quantitation of levamisole in forensic drug samples that utilizes an ion-mobility-based separation combined with mass spectrometry [ 34 ]. DMS-MS has been demonstrated to show enhanced selectivity and specificity as well as higher throughput compared to GC-and LC-based methods [ 34 ].…”
Section: Emerging Methods For Measurement Of Levamisolementioning
confidence: 99%
“…DMS-MS has been demonstrated to show enhanced selectivity and specificity as well as higher throughput compared to GC-and LC-based methods [ 34 ]. Moreover, it eliminates the need for extensive and timeconsuming sample extraction as required by GC-MS and some LC-MS/MS methods.…”
Section: Emerging Methods For Measurement Of Levamisolementioning
confidence: 99%
“…Such street drugs are often ''cut'' with diluents to add bulk to the sample sold, thereby increasing profits for the drug dealer or manufacturer. Common cutting agents can include stimulants or anesthetics having their own central nervous system effects, such as benzocaine, lidocaine, and caffeine [10,20]. Indeed, work by Brandt and coworkers has shown that common cathinone mixture additives include these stimulants, among other compounds [9,10,14].…”
Section: Introductionmentioning
confidence: 96%
“…Generally, this extensive fragmentation means that mass spectra across this class of compounds are similar enough to impede the ability to distinguish between cathinones. Ultimately, the limitations associated with conventional methods for cathinone testing and analysis, the inclusion of multiple cathinones or adulterants in a single product, and the constantly changing ingredient profiles, all contribute to the sample testing backlogs that are a growing problem for U.S. crime labs and enforcement agencies [18,20]. With the continual expanding and changing field of designer drug abuse, high throughput, informative methods are needed to keep pace with ever increasing casework.…”
Section: Introductionmentioning
confidence: 98%